Laryngotracheal Involvement in Systemic Light Chain Amyloidosis - Ginat, Daniel T. (Head Neck Pathol, 2017)
Laryngotracheal amyloid deposition is an uncommon manifestation of systemic light chain amyloidosis. Diagnostic imaging, such as CT, is useful for suggesting the possibility of amyloidosis and delineating the extent of the lesions for surgical management; however, the diagnosis is confirmed with the histologic finding of amorphous eosinophilic material which stains positively for Congo red and may show apple green birefringence on polarization. These features are exemplified in this sine qua non radiology-pathology correlation article.